2020
DOI: 10.1039/c9qi01119f
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to secondary building units of metal–organic frameworks for the development of new functions

Abstract: Post-synthetic modification methods for the secondary building units in MOFs facilitate unique structures and properties that are impossible to access via direct syntheses, which can be classified as four categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 126 publications
0
39
0
Order By: Relevance
“… 1 5 The unique possibility of their further postsynthetic modification offers a convenient way of introducing new functionalities into a system, 6 , 7 for example, by direct functionalization of metal nodes. 8 This approach is of high relevance in reactions where multiple chemical components are required for the catalytic cycle (e.g., catalytic cycloaddition of CO 2 to reactive substrates). 9 …”
Section: Introductionmentioning
confidence: 99%
“… 1 5 The unique possibility of their further postsynthetic modification offers a convenient way of introducing new functionalities into a system, 6 , 7 for example, by direct functionalization of metal nodes. 8 This approach is of high relevance in reactions where multiple chemical components are required for the catalytic cycle (e.g., catalytic cycloaddition of CO 2 to reactive substrates). 9 …”
Section: Introductionmentioning
confidence: 99%
“…Secondary building units (SBUs) are the metal cluster ions that are bonded through non-metal atoms and act as catalytic centers in photocatalytic reactions [23]. This also helps to tune the bandgap in MOFs.…”
Section: Secondary Building Unitmentioning
confidence: 99%
“…Through a large number of explorations, it has been found that MOFs can be a good candidate for proton conductors for the following reasons: first, the porous structures of MOFs contain rich H-bonds and water clusters, which can carry out proton transmission quickly and efficiently; second, the single crystal products of MOFs are relatively easy to obtain, and their fine structural characteristics can be obtained through X-ray crystallography, which provides convenience for the exploration of the proton conduction mechanism; third, the proton conductivity of MOFs can be tuned by selecting different metal ions or modifying multifunctional organic ligands or the post-modification method. Although the research on the proton conductivity of such MOFs has been summarized and evaluated by several groups covering phosphate MOFs, 32 carboxylate MOFs, 33 and so on, [34][35][36][37][38][39] most of these reviews are broad and do not include specific reviews of MOFs of a certain metal atom, especially zirconium-based MOFs. It has been found in past studies that a significant number of proton conducting MOFs are of low stability, which limits their further practical application.…”
Section: Introductionmentioning
confidence: 99%